Stabilized Pd Nanoparticles Encapsulated in MIL‐101(Cr) for Chemoselective Hydrogenation of Polyunsaturated FAMEs - Yardthip Preedawichitkun; Natthida Numwong; Narong Chanlek; Po‐Wen Chung; Raju Kumar; Chularat Wattanakit; Warot Prasanseang; Pratya Promchana; Chanisara Nooto; Phuwadon Khenkhom; Kittisak Choojun; Tawan Sooknoi (ChemCatChem, 2025)
Abstract Palladium nanoparticles (Pd NPs) were successfully encapsulated within the porous framework of MIL‐101(Cr) via a double solvent method to produce highly dispersed and stable catalysts for the chemoselective hydrogenation of polyunsaturated fatty acid methyl esters (FAMEs). Pd loadings ranging from 0.5 to 1.5 wt.% were systematically studied to elucidate the effects of nanoparticle size, dispersion, and hydrogen activation behavior on catalytic performance. The 0.8Pd/MIL‐101(Cr) catalyst exhibited the highest turnover frequency (TOF ∼9,700 h −1 ) and superior selectivity (>90%) toward monounsaturated products (C18:1), attributed to optimal Pd dispersion. In contrast, the 0.5Pd/MIL‐101(Cr) showed an induction period under low H 2 partial pressure, indicating limitations in hydride accommodation, while the 1.5Pd/MIL‐101(Cr) suffered from Pd aggregation, resulting in a reduced intrinsic activity. Product selectivity was primarily governed by overall conversion: C18:1 was favored at low conversions, whereas C18:0 formation increased at higher conversions due to secondary hydrogenation. The catalysts demonstrated excellent stability and recyclability over multiple cycles without detectable Pd leaching or structural degradation. These findings establish MIL‐101(Cr) as a robust and tunable platform for dispersing Pd NPs and highlight the potential of Pd/MIL‐101(Cr) catalysts for efficient, selective upgrading of bioderived feedstocks under mild reaction conditions.
Keywords: Catalysis and Hydrodesulfurization Studies; Catalysis for Biomass Conversion; Asymmetric Hydrogenation and Catalysis